HGG-37. DETECTION OF IDH1 R132H MOSAICISM IN ANAPLASTIC ASTROCYTOMA PATIENTS. Issue 2 (22nd June 2018) - Lee, Sulgi; Bornhorst, Miriam; Panditharatna, Eshini; Kambhamptai, Madhuri; Turner, Joyce; Packer, Roger J; Kilburn, Lindsay; Nazarian, Javad
Abstract: Anaplastic astrocytomas are aggressive glial cancers that present poor prognosis and high recurrence. Heterozygous mutations in the IDH1 (R132H) gene are common in adult anaplastic astrocytomas, but are uncommon in the pediatric population. In a majority of cases, the IDH1 R132H mutation is somatic, although rare cases of anaplastic astrocytoma have been described in patients with mosaic germline mutations of IDH1 (Ollier disease or Maffucci syndrome). Here, we present two siblings who developed IDH1 R132H mutant high grade astrocytomas at 15 and 26 years of age. Our analysis of IDH1 R132H mutations in the siblings' tumors and non-neoplastic tissues, including healthy regions of the brain (post-mortem samples from one sibling), cheek cells and primary teeth identified IDH1 R132H mosaicism, using digital PCR system. While both tumors had IDH1 R132H mutant allelic frequencies around 50%, mutant allelic frequencies ranging from 0.01% to 0.64% were detected in teeth, cheek cells, blood and non-tumorous brain tissue. Whole exome sequencing of the tumor tissue did not reveal any other common mutations between the two siblings. Our study demonstrates an example of IDH1 R132H mosaicism in two siblings with anaplastic astrocytoma, which could have gone unnoticed by traditional sequencing technologies. This finding supports a trend, seen in other cancers, of mosaic-like mutant allelic gene frequencies associated with cancer development. Further large-scale studies are needed to better understand the prevalence of mosaic IDH1, or other mutations, in patients with brain tumors, as this could impact the diagnosis and management of these patients.